The effects of students' entrepreneurial characteristics on their propensity to become entrepreneurs in Malaysia - Che Embi, Nor Azizan; Jaiyeoba, Haruna Babatunde; Yussof, Sheila Ainon (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this paper is to reflect on the data collected from Malaysian students to investigate the effects of students’ entrepreneurial characteristics (need for achievement, locus of control, propensity to take risk, self-confidence, tolerance of ambiguity and uncertainty, and leadership) on their propensity to become entrepreneurs in Malaysia. Design/methodology/approach – As a quantitative study, various analyses, such as exploratory factor analysis, confirmatory factor analysis and structural equation modelling, were conducted to analyze the data collected from 257 students known to have participated in entrepreneurship course and programmes. Findings – The results show that leadership skill, need for achievement, tolerance of ambiguity, and risk-taking propensity are positively and significantly associated with students’ intention to initiate entrepreneurial activities in Malaysia. Originality/value – The researchers have used data from the perspective of Malaysian students to increase the readers’ understanding on students’ entrepreneurial characteristics that could enhance their likelihood to become entrepreneurs in Malaysia.